Hemothorax resulting from an initially masked aortic perforation caused by penetration of the sharp edge of a fractured rib: A case report. (2020) - Goda, Yasufumi; Shoji, Tsuyoshi; Date, Naoki; Katakura, Hiromichi
Highlights: Rare aortic injury from a rib fracture, which is not found in primary evaluation. Hemothorax with great vessel injury can be fatal and should be detected using computed tomography. Some great vessel injuries cannot be detected through contrast-enhanced chest computed tomography. Great vessel injury should be considered in hemothorax with multiple rib fractures. Abstract: Introduction: There are multiple causes of hemothorax in blunt chest trauma. However, a traumatic hemothorax with an uncertain cause is potentially life-threatening without treatment, because an undetected and hidden great vessel injury can remain unknown. Delayed diagnosis can lead to death. Presentation of case: A 77-year-old man was transferred to a local hospital, after experiencing a 3-m fall. Contrast CT of the chest revealed a left clavicle fracture, multiple left rib fractures and hemopneumothorax, but no obvious signs of great vessel injury, such as aortic injury. His condition was stable, owing to the chest tube thoracostomy with 800 ml blood output and intravenous fluid. The patient was then transferred to our hospital for further treatment. However, his condition rapidly deteriorated in the ambulance on the way to our hospital, and he needed a blood transfusion. On arrival, he was in shock, with his vital signs compromised due to blood loss. Emergency open thoracotomy was performed to explore the bleeding point and stop hemorrhaging. Intraoperative findings revealed sharp edges of the fractured fourth and fifth left ribs to be protruding into the chest cavity toward the descending aorta and causing an aortic pinhole injury. Ruptured aorta was repaired with a pledget-armed sutures and the sharp fractured ribs were resected. The patient was discharged, uneventfully, 35 days after the operation. Conclusion: This case suggests that even if great vessel injury is not detected on contrast CT at admission, it should always be considered especially in a hemothorax case with multiple rib fractures.